Effects of enzymatic clarification treatment on phenolic compounds of pummelo (Citrus grandis L. Osbeck) fruit juice - Abdul Karim Shah, Nor Nadiah; Abdul Rahman, Russly; Shamsuddin, Rosnah; Mohd Adzahan, Noranizan (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Pummelo is known to be the largest of all citrus fruits, with expected ratio of 2:1 (w/v) of producing juice, is an attractive opportunity for Malaysia to expand pummelo’s influence and marketability over the international market of juices. However, in order to obtain a bright and clear product, the juice must be clarified and it is expected to affect the phenolic composition. The purpose of this study is to investigate the changes that occur during enzymatic clarification on the phenolic compounds between 2 varieties of pummelo juice: Ledang (PO55) and Tambun (PO52). The changes in the polyphenols composition are monitored through the clarification process using High Performance Liquid Chromatography Diode Array Detection (HPLC-DAD). Clarification of pummelo fruit juice with Pectinase SMASH XXL has statistically no significance influence (p <0.05) on the phenolic compounds of Ledang and Tambun variety. However, the phenolic compounds (naringin) of Tambun variety is statistically high (p >0.05) when compared to Ledang variety and no significant difference was found to naringin’s amount after the enzymatic treatment. This study suggests that Pectinase SMASH XXL is to be used as recommended to avoid unfavourable changes to the juice quality while producing a healthy, organic and profitable product.